Scanned ion beam therapy for prostate carcinoma - Hild, Sebastian; Graeff, Christian; Ruciński, Antoni Wojciech; Zink, Klemens; Habl, Gregor; Durante, Marco; Herfarth, Klaus; Bert, Christoph (Strahlentherapie und Onkologie, 2016)
Intensity-modulated particle therapy (IMPT) for tumors showing interfraction motion is a topic of current research. The purpose of this work is to compare three treatment strategies for IMPT to determine potential advantages and disadvantages of ion prostate cancer therapy.